Acupuntura veterinária em pequenos animais - Taguti, Érika Mari [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Acupuncture is one of the oldest forms of treatment, which is based in the grounds of Traditional Chinese Medicine. Despite the ancient history, it’s not completely widespread in Brazil, neither so comprehensive in veterinary medicine as used in humans. The technique of inserting needles into acupuncture points, can also be stimulated by heat, electrical stimulation or implants of metal, is mainly focused on neuromuscular disorders in small animals. The difficulty of comprehension of language and the lack of cientific bases restricted the possible applications of acupuncture. This work will address some of the clinical situations this complementary treatment can act, such as neurological, cardiorespiratory, reproductive, gastrointestinal, immunological, and postoperative intensive care

A acupuntura é uma das artes de tratamento mais antigas, cuja base está nos fundamentos da Medicina Tradicional Chinesa. Apesar do histórico milenar, ainda não é totalmente difundida no Brasil, nem tão abrangente em Medicina Veterinária quanto à utilizada em humanos. A técnica de inserção de agulhas em acupontos, que também podem ser estimulados por calor, estímulos elétricos ou implantes de metais, é centrada principalmente em distúrbios neuromusculares em pequenos animais. A dificuldade de compreensão da linguagem e a carência sobre as bases científicas restringiram as possíveis aplicações da acupuntura. Portanto, neste trabalho serão abordadas algumas das situações clínicas que este tratamento complementar pode atuar, tais como, distúrbios neurológicos, cardiorrespiratórios, reprodutivos, gastrointestinais, imunológicos, pós-operatório e cuidados intensivos
Keywords: Acupuntura veterinaria; Veterinária de pequenos animais; Acupuncture - Veterinary Medicine